2009
DOI: 10.4012/dmj.28.307
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal efficacy of glycine-type amphoteric surfactant as a denture cleaner and its influence on properties of denture base resins

Abstract: The bactericidal efficacy of 1.00-4.50% glycine-type amphoteric surfactant (Gly) was evaluated by measuring its microorganism removal rate in denture plaque. Physical and mechanical properties such as surface roughness, color difference, and bending strength of two different denture base resins were determined before and after cleaning in Gly solutions, a commercial denture cleaner, and tap water. The microorganism removal rates of all the Gly solutions were higher than those of a commercial enzymatic denture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 16 publications
(17 reference statements)
3
33
1
Order By: Relevance
“…Recent studies have shown that powders based on glycine, due to their low abrasiveness, can be safely applied subgingivaly during maintaining periodontal treatment to remove both supra-and subgingival plaque thereby reducing the harm to root surfaces. 35,36,37 Glycine has amphoteric characteristics and a pH ranging from acidic to alkaline. Although glycine possesses the washing action of anionic surfactant and the bactericidal action of cationic surfactant, its acidic pH may negatively influence the capacity of reduction of dentine permeability in a wet environment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that powders based on glycine, due to their low abrasiveness, can be safely applied subgingivaly during maintaining periodontal treatment to remove both supra-and subgingival plaque thereby reducing the harm to root surfaces. 35,36,37 Glycine has amphoteric characteristics and a pH ranging from acidic to alkaline. Although glycine possesses the washing action of anionic surfactant and the bactericidal action of cationic surfactant, its acidic pH may negatively influence the capacity of reduction of dentine permeability in a wet environment.…”
Section: Discussionmentioning
confidence: 99%
“…Alone, it recreates 408 the same antibiotic -enhancing effect demonstrated by JBS. SLAA is an amphoteric 409 surfactant, with limited data demonstrating some anti-bacterial activity, 42,43 however, to our 410 knowledge this is the first study to show the anti-biofilm activity of SLAA. Amphoteric 411 compounds, being both anionic and cationic, have an advantage in that they have both the 412 detergent activity seen with anionic compounds and the bactericidal activity seen with 413 cationic compounds.…”
mentioning
confidence: 91%
“…However, the differences disappeared on day 7, except for the finding that Ag-Pd-Au still had the lowest values. We expected that the resin used as a control would have more adherence by biofilms than alloy samples, because resin is thought to be easily absorbed by denture plaque 17) . However, to our surprise, the amount of adherent biofilm on the resin sample was significantly lower than that of all of the alloys except Ag-Pd-Au on both overnight and day 4 (p<0.05).…”
Section: Quantitative Analysis Of Biofilms On the Samplesmentioning
confidence: 99%
“…Denture plaque easily adheres to the resin denture base 17) , because the surface of the acrylic resin is porous. Another problem associated with resin dentures is their weak mechanical strength when compared to metal base dentures.…”
Section: Introductionmentioning
confidence: 99%